2014
DOI: 10.1371/journal.pone.0108363
|View full text |Cite
|
Sign up to set email alerts
|

Diversity and Localization of Bacterial Endosymbionts from Whitefly Species Collected in Brazil

Abstract: Whiteflies (Hemiptera: Aleyrodidae) are sap-sucking insect pests, and some cause serious damage in agricultural crops by direct feeding and by transmitting plant viruses. Whiteflies maintain close associations with bacterial endosymbionts that can significantly influence their biology. All whitefly species harbor a primary endosymbiont, and a diverse array of secondary endosymbionts. In this study, we surveyed 34 whitefly populations collected from the states of Sao Paulo, Bahia, Minas Gerais and Parana in Bra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
80
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 66 publications
(89 citation statements)
references
References 69 publications
8
80
1
Order By: Relevance
“…However, a peculiar sub-localization pattern was observed for H. defensa and for Wolbachia in eggs. Strong H. defensa-specific probe signals were detected in the head and in the region associated with the male reproductive organs, which is in sharp contrast with previous studies (Marubayashi et al 2014), which found this bacterium always confined to the bacteriosome in MEAM 1 and New World 2 species from Brazil. In addition, our results reinforced the notion that H. defensa is also associated with B. tabaci MEAM 1 population.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…However, a peculiar sub-localization pattern was observed for H. defensa and for Wolbachia in eggs. Strong H. defensa-specific probe signals were detected in the head and in the region associated with the male reproductive organs, which is in sharp contrast with previous studies (Marubayashi et al 2014), which found this bacterium always confined to the bacteriosome in MEAM 1 and New World 2 species from Brazil. In addition, our results reinforced the notion that H. defensa is also associated with B. tabaci MEAM 1 population.…”
Section: Resultscontrasting
confidence: 99%
“…Although whitefly endosymbionts have been object of many recent studies worldwide, there is an overall few works documenting the endosymbiont diversity in whiteflies populations colonizing the tomato crop in Brazil (Marubayashi et al 2013(Marubayashi et al , 2014. Currently, the secondary endosymbiont Wolbachia is being a subject of extensive studies in many different organisms, mainly because it can manipulate the reproduction rate of their hosts and enhance their own rate of transmission and therefore might serve as a biological control agent (Mitsuhashi et al 2002).…”
Section: Introductionmentioning
confidence: 99%
“…The authors correlated this disease with whiteflies in the studied area and a similar trend was observed in the present investigation [36]. A similar study has also been reported in Brazil, where the endosymbiont population was found to be significantly different in different areas [51].…”
Section: Resultssupporting
confidence: 91%
“…The Aleyrodidae fly population was found to be significantly different in selected regions, and endosymbionts of Hamiltonella, Rickettsia, Fritschea, Cardinium, Arsenophonus, and Wolbachia were recorded in promotions to the Aleyrodidae fly population. The Hamiltonella co-infection percentages in Faisalabad, Chiniot, Sargodha, Jhang, T. T. Singh, and Burewala were recorded as 51,28, 75,8,23, and 25, respectively, whereas relative abundance percentages of Hamiltonella endosymbiont were recorded as 52, 35, 65, 5, 20, and 21 in Faisalabad, Chiniot, Sargodha, Jhang, T. T. Singh, and Burewala, respectively. A similar trend was observed for Rickettsia, Fritschea, Cardinium, Arsenophonus, and Wolbachia co-infection and relative abundances.…”
mentioning
confidence: 95%
“…Some of these species, in particular the B and Q biotypes, are highly invasive and well studied. No correlation was found between a certain B. tabaci species and secondary symbionts on a global scale because the same species may harbor a certain bacterium in one geographical area and not in the other [97][98][99]. Such is the case with Hamiltonella; in Israel, populations of the B species carry Hamiltonella while Q populations do not.…”
Section: Whiteflies and Secondary Symbiontsmentioning
confidence: 99%